Mobile money as a sustainable alternative for SMEs in less developed financial markets - Robertson Khan Tengeh; Frank Sylvio Gahapa Talom (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Despite the many advantages that mobile money offers to Small and Medium-sized Enterprises (SMEs) relative to traditional banking services, the majority of stakeholders of this platform have not yet maximised its use owing to several concerns not limited to trust, awareness, and even cost. To examine the factors justifying the adoption and usage of Mobile Money Services (MMS) among SMEs, the types of Mobile Money Services used by these SMEs, and the interdependences between these variables, this study adopted an exploratory approach. The researchers elected to use a mixed-method approach, which necessitated the usage of a survey questionnaire and structured in-depth interviews. Representatives of 12 SMEs were interviewed during the qualitative phase to corroborate the 285 SMEs surveyed in the quantitative part of the study. Descriptive and inferential statistics were adopted to analyse the quantitative data using the Statistical Packages for Social Sciences version 26 (SPSS version 26). The researchers described the qualitative data according to themes, and the findings were combined after that. While no single factor was accountable, it emerged that accessibility, safety, and convenience were the main factors that entice SMEs in Douala, Cameroon to embrace mobile money services in the effort to receive money from clienteles, pay suppliers, and purchase airtime for additional transactions (most preferred mobile money services). Furthermore, it was found that there was a statistically significant association between most of the motivating factors cited and the most preferred mobile money services used by SMEs in Douala. These findings validate the role that mobile money plays in promoting the inclusive finance agenda for SMEs, mainly in the context of emerging economies where the majority of people and businesses do not have access to banking services and therefore may be of interest to policymakers and different stakeholders. Furthermore, an identification of the types of mobile money services businesspersons mostly use in Douala, a business hub, may help to develop businesses by directing the stakeholders to agenda items of interest in the context of Cameroon.
Keywords: 650; SMEs; innovation; business development; Cameroon; digital financial services; Douala; financial performance; micro finance; mobile money; payments and receipts